Coronary lesions in refractory out of hospital cardiac arrest (OHCA) treated by extra corporeal pulmonary resuscitation (ECPR). (May 2018) - Lamhaut, Lionel; Tea, Victoria; Raphalen, Jean-Herlé; An, Kim; Dagron, Christelle; Jouffroy, Romain; Jouven, Xavier; Cariou, Alain; Baud, Frédéric; Spaulding, Christian; Hagege, Albert; Danchin, Nicolas; et al.
Abstract: Purpose: Extracorporeal cardiopulmonary resuscitation (ECPR) is a second line treatment for refractory cardiac arrest (R-OHCA). Timing of ECPR before performing coronary angiography (CAG) is still debated. The aim of the study was to describe the clinical and angiographic characteristics of the largest cohort of out-of-hospital cardiac arrest (OHCA) patients undergoing ECPR. Methods: All refractory OHCA patients with ECPR managed by the prehospital mobile intensive care unit (MoICU of the SAMU) in Paris (France) were prospectively included from October 2014 to December 2016. Results: Among 74 patients included over the period, 54 patients had coronary artery disease (CAD). There is a trend toward the CAD patients being older but it did not meet statistical significance (55.3 ± 11.8 vs. 50.6 ± 12.8, p = 0, 14). Patients were more frequently men and smokers (p = 0.03 for both). The proportion of initial shockable rhythm tended to be higher in patients with CAD (71% vs. 55%). The rate of 1-, 2-, and 3-vessel disease were 43%, 35% and 22% respectively. The Syntax Score was 18 ± 9 and the lesions in each epicardial vessel were mainly proximal. Percutaneous coronary intervention was performed ad hoc in 49 patients (91%). Complete revascularization was performed in 64%. Inhospital death was numerically lower (65% vs. 75%) in patients with CAD, especially in patients with initial shockable rhythm. Conclusion: In 74 refractory OHCA patients treated with ECPR implanted by a prehospital mobile intensive care unit, the rate of CAD was high (54/74) especially in patients with shockable rhythm. The majority of patients presented with double or triple vessel disease and proximal lesions. The severity and extension of CAD may explain the refractory nature of the cardiac arrest.